DESEMPENHO TÉRMICO DE ÁTICOS COM ISOLAMENTO TÉRMICO REFLEXIVO: ESTUDO EM UMA BANCADA EXPERIMENTAL - Michels, Caren; Güths, Saulo (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
One of the major worries arisen in the past years concerns the quantity of energy spent in order to provide thermal comfort in buildings, since a large part of this energy results from the heat transference through the coverage. Encouraging the reduction of thermal gain through this surface is one of the ways to decrease the expenses with energy and to provide thermal comfort. This research aims to evaluate the thermal performance of attics with and without reflective thermal insulation in the summer and winter by experimental measurements. To this end, a testing workbench was built and four samples of coverage were evaluated. All samples contained fiber cement tiles and concrete slab, one of which was used as the reference, two present reflective thermal insulation and the last is formed by white tiles. Results showed that the use of reflective thermal insulation increased the attic thermal resistance in both seasons. In the descendant heat flow (summer), the attic thermal resistance was higher than in the ascendant flow (winter). Regarding the white tiles effect, there was a decrease in the superficial temperatures and the diurnal heat transference in both seasons.